An Overview of the Condition of Clean Water Facilities in Titi Papan Village, Medan Deli District - Azzahra, Fatimah; Nanda, Meutia; Nasution, Dinda Azria; Muharani, Anisa; Audina, Salsabila (PROMOTOR, 2024)
Clean water is water that can be used for everyday life, if it meets predetermined health standards, it can be used in everyday life. One of the main problems faced is the lack of availability of clean water sources and the uneven distribution of clean water supply services, especially in rural areas. The aim of this research is to provide an overview of the condition of clean water facilities in Titi Papan Village, Medan Deli. This research uses a quantitative approach with descriptive research type. The population of this research is the entire community in Titi Papan sub-district, totaling 3,377 families with sampling using non-probability sampling techniques, specifically accidental sampling, totaling 97 families. The results of the research show that 21% of the people in Titi Papan Village have access to clean water, 52% of the people whose source of clean water is using dug wells, and 65.2% of the people who have difficulty accessing clean water. The conclusion from this research is that the majority of people in Titi Papan Village, Kec. Medan Deli does not yet have clean water available, where the average community uses a source of clean water that comes from dug wells and also because access to clean water is difficult for the community to reach, therefore people prefer to use dug wells rather than PDAM. Therefore, it is recommended to carry out a socialization or education program for the community about the importance of good clean water management and also the need for cooperation and collaboration between the central government, regional government and the private sector in the issue of providing clean water in Titi Papan Village, Kec. Denai Field.